STUDI SIMULASI KURVA HISTERESIS BAHAN FERROELEKTRIK BERBASIS TEORI DINDING DOMAIN MENGGUNAKAN MODEL LANGEVIN DAN ISING SPIN - Hamid, D. Triyono (Program Studi Pendidikan Fisika dan Program Studi Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2014)
This paper addresses the modeling of hysteresis in ferroelectric materials through consideration of domain wall theory. The model is developed in two steps. In the first step, anhysteresis relation of Langevin and Ising spin is obtained with dipol interaction. In the second step, hysteresis is incorporated through consideration of domain wall theory. Curve model is validated through curve experiment PMN-PT-BT [ Pb(Mg,Nb)O3-PbTiO3-BaTiO3 ] material. Pearson coefficient for curve model is more than 0.99. So curve model is valid. Curve hysteresis ferroelectric studies of PZT4, PZT5A, PZT5H, PMNT [ Pb(Mg,Nb)TiO3 ] single crystal, BZT [ Ba(Zr,Ti)O3)], BT-BZ (BaTiO3-BaZrO3) thin film and PZT [ Pb(Zr,Ti)O3 ] thin film materials yields Pearson coefficient more than 0.97 for Langevin and Ising spin model. It shows that Langevin or Ising spin model is good for studying hysteresis curve of ferroelectric materials. PZ26 (PbZrO3) material is not appropriate with model based on domain wall theory, because of asymetri curve. Keywords : ferroelectric, domain wall of ferroelectric, hysteresis of ferroelectric, Langevin model, Ising spin model.